2018
DOI: 10.1007/s10955-018-2033-x
|View full text |Cite
|
Sign up to set email alerts
|

Tightness of the Ising–Kac Model on the Two-Dimensional Torus

Abstract: We consider the sequence of Gibbs measures of Ising models with Kac interaction defined on a periodic two-dimensional discrete torus near criticality. Using the convergence of the Glauber dynamic proven by H. Weber and J.C. Mourrat [MW17a] and a method by H. Weber and P. Tsatsoulis employed in [TW16], we show tightness for the sequence of Gibbs measures of the Ising-Kac model near criticality and characterise the law of the limit as the Φ 4 2 measure on the torus. Our result is very similar to the one obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Inspired by this result, our aim here is to show how these recent ideas connecting probability with PDE theory can be streamlined and extended to recover a complete, self-contained and simple, proof of existence of the Φ 4 3 measure on the full space. In the same spirit see also the work of Hairer and Iberti [HI18] on the tightness of the 2d Ising-Kac model. Soon after Hairer's seminal paper [Hai14], Jaffe [Jaf14] analyzed the stochastic quantization from the point of view of reflection positivity and constructive QFT and concluded that one has to necessarily take the infinite time limit to satisfy RP.…”
Section: Introductionmentioning
confidence: 80%
“…Inspired by this result, our aim here is to show how these recent ideas connecting probability with PDE theory can be streamlined and extended to recover a complete, self-contained and simple, proof of existence of the Φ 4 3 measure on the full space. In the same spirit see also the work of Hairer and Iberti [HI18] on the tightness of the 2d Ising-Kac model. Soon after Hairer's seminal paper [Hai14], Jaffe [Jaf14] analyzed the stochastic quantization from the point of view of reflection positivity and constructive QFT and concluded that one has to necessarily take the infinite time limit to satisfy RP.…”
Section: Introductionmentioning
confidence: 80%
“…For a proof of restricted Markov uniqueness of dynamics associated with the Φ 4 2 -model see [87], which uses also results of [74], [74] providing also a new construction of strong solutions in certain negative index Besov spaces for this stochastic quantization equation. For a derivation of the stochastic quantization equation from Kac-Ising models see [35], [41], [55] and [72]. For work on Gaussian white noise driven PDEs related to other models of quantum fields in 2-dimensional space-time see [2], [9] and [59].…”
Section: The Construction Of a Corresponding φmentioning
confidence: 99%
“…Let us also mention that a derivation of the SQE for the ϕ 4 2 -model on R 2 from a Kac-Ising model has been achieved in [146]. This goes back to work initiated in [79] for d = 1 and conjectured results in [90] for d = 2, 3 (see also [110]). The SQEs for the exponential/trigonometric models on R 2 have been discussed by Dirichlet forms in [18] and by semigroup methods, similarly as in [22] (the latter for the ϕ 4 3 -model on T 3 ).…”
Section: Introduction 1backgroundmentioning
confidence: 69%